2018
DOI: 10.3233/nre-172381
|View full text |Cite
|
Sign up to set email alerts
|

Return to learn: Transitioning to school and through ascending levels of academic support for students following a concussion

Abstract: Allowing school districts to direct the application of existing ascending levels of educational support for students with concussion as they return to school can promote robust and positive outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 6 publications
0
40
0
Order By: Relevance
“…The majority of students will only require informal post‐concussion supports provided by teachers and monitored by the school‐based concussion management team. Schools are required to support all students experiencing learning or behavior impacts resulting from a medical, psychological, behavioral, or social condition 30 . Consensus participants recommend that schools consider concussion as a health condition that naturally falls within a school's existing system of supports.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of students will only require informal post‐concussion supports provided by teachers and monitored by the school‐based concussion management team. Schools are required to support all students experiencing learning or behavior impacts resulting from a medical, psychological, behavioral, or social condition 30 . Consensus participants recommend that schools consider concussion as a health condition that naturally falls within a school's existing system of supports.…”
Section: Discussionmentioning
confidence: 99%
“…9,11,18 Our finding that adequate school accommodations were associated with improved school HRQOL in SRC patients provides support for providing SRC patients with return-to-learn programs that allow students to make a gradual return to school and help minimize cognitive-related symptoms. 20,32,33 Future studies are needed to address the added clinical value of incorporating patient-reported HRQOL outcome measures into the standardized management of patients with acute concussion and PCSS.…”
Section: Discussionmentioning
confidence: 99%
“…Return to learn is the process of transitioning back to the classroom following concussion using individualised academic adjustments87 88 (see table 4). School personnel should be informed of the injury and implement an initial school support plan without delay 89. Many concussed athletes recover quickly enough to return to the classroom with no or very brief adjustment of academic activities, but schools should be prepared to provide additional support in the event that recovery takes longer.…”
Section: Management Of Concussionmentioning
confidence: 99%